2000
DOI: 10.1071/ah000115
|View full text |Cite
|
Sign up to set email alerts
|

Hospital outpatient and emergencyservices in rural Victoria

Abstract: Outpatient and emergency services in rural hospitals have rarely been studied. This paper analyses routinely collecteddata, together with data from a survey of hospitals, to provide a picture of these services in Victorian public hospitals.The larger rural hospitals provide the bulk of rural outpatients and emergency services, particularly so for medicaloutpatients. Cost per service varies with the size of the hospital, possibly reflecting differences in complexity. Fundingpolicies for rural hospital outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 3 publications
0
15
1
Order By: Relevance
“…The proportion of ATS category 5 of total presentations for subregional health services is twice that of metropolitan hospitals. In previous work, Duckett and Kenny (2000) described the range of emergency presentations at smaller rural hospitals in Victoria as 'similar to that found in community services' (Duckett & Kenny 2000, p. 124). The role of rural hospitals in the provision of primary health care is increasing as a result of GP-led primary care services not meeting the growing demand for them (Department of Human Services 2007).…”
Section: Emergency Presentation Profilementioning
confidence: 79%
See 2 more Smart Citations
“…The proportion of ATS category 5 of total presentations for subregional health services is twice that of metropolitan hospitals. In previous work, Duckett and Kenny (2000) described the range of emergency presentations at smaller rural hospitals in Victoria as 'similar to that found in community services' (Duckett & Kenny 2000, p. 124). The role of rural hospitals in the provision of primary health care is increasing as a result of GP-led primary care services not meeting the growing demand for them (Department of Human Services 2007).…”
Section: Emergency Presentation Profilementioning
confidence: 79%
“…To reverse this trend so that nurses in rural health services manage more patients with less medical intervention, further education and training may be needed to advance their practice. It has been found that many nurses working in small rural hospitals providing emergency care do not have the competencies to operate with less medical support, including advanced life support competencies (Duckett & Kenny 2000, Kenny & Duckett 2003). Arguably, these nurses are most in need of these advanced skills, for without them the nurses will be unable to respond adequately and confidently to emergency presentations that need treatment urgently and will certainly not be able to reduce their calls on doctors for less urgent presentations.…”
Section: Discussion – Reconceptualising a Model Of Rural Practicementioning
confidence: 99%
See 1 more Smart Citation
“…2000, Humphreys et al. 2002) and small rural hospitals struggle to maintain adequate services (Duckett & Kenny 2000). Similar issues that threaten the sustainability of rural hospitals, such as workforce shortages, financial difficulties, increased need for capital, competition for market share and the impact of the shift from inpatient to outpatient care on hospital function, have been identified internationally (Moscovice & Rosenblatt 2000, Ricketts 2000, Trinh & O'Connor 2000, Basu & Friedman 2001).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Current definitions of rural nursing generally focus on geographic location, population size and lack of, or limited, access to, medical practitioners (Kreger 1991; Thornton 1992; Hegney, McCarthy and Pearson 1999) Within rural Australia, nurses practise in a variety of locations; however, in Victoria, the majority are employed in rural hospitals. The heterogeneity of rural hospitals and the diversified services that are offered (Duckett and Kenny 2000) require nurses to be multiskilled practitioners with a broad knowledge and skill base (Hegney and McCarthy 2000; Witham 2000; Francis, Bowman and Redgrave 2001).…”
Section: The Complexity Of the Rural Nursing Rolementioning
confidence: 99%